The Contribution of Tour Companies Towards the Development of the Tourism Industry in Rwanda: A Case Study of Primate Safari Tour Company - Diogene, Habimana (Kabale University, 2019)
A Dissertation Submitted in Partial Fulfillment of the Requirement for the A Ward of the Degree in Tourism of Kabale University.